2011
DOI: 10.2459/jcm.0b013e3283448695
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on long-term follow-up of percutaneous coronary intervention based on clinical presentation of coronary artery disease

Abstract: No significant interaction between diabetes mellitus and clinical presentation was noted in this study. The high rates of cardiac events observed in diabetes mellitus patients despite recent advances in interventional techniques outline the need for a multidisciplinary approach in the management of diabetes mellitus patients, including optimization of glycemic control, aggressive medical therapy and more complete coronary revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…In our study, the relatively high prevalence of diabetes in AMI patients (27.4%) is within the previously reported range of 14% to 34% (18, 24, 28). The diabetic patients also had more traditional risk factors, such as high BMI, hypertension, dyslipidemia and previous history of ischemic heart disease (24, 29).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the relatively high prevalence of diabetes in AMI patients (27.4%) is within the previously reported range of 14% to 34% (18, 24, 28). The diabetic patients also had more traditional risk factors, such as high BMI, hypertension, dyslipidemia and previous history of ischemic heart disease (24, 29).…”
Section: Discussionsupporting
confidence: 91%
“…Eleven studies [7,8,11,14,1618,20,26,28,33] as well as our data reported TVR; the pooled analysis showed that DM patients had a higher incidence of TVR (RR = 1.40, 95% CI 1.24–1.59, I 2  = 43%) (Fig. 2).…”
Section: Resultssupporting
confidence: 59%
“…[ 12 , 13 ] However, compared with non-DM patients, DM patients still have a high risk of major adverse cardiac events (MACEs) with DES. [ 14 16 ] Some studies found that the incidence of cardiac death between patients with or without DM is similar. [ 17 ] But some other large sample clinical trials found that patients with DM still had a higher risk of MACE even with DES.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, concerns arose in the planning of the study by Ruperto et al 1 There is a lack of data on the prognostic importance of silent ischemia in totally asymptomatic patients and, particularly, on a possible benefit of medical and interventional therapy in such patients.…”
mentioning
confidence: 93%
“…The retrospective study by Ruperto et al 1 investigates the influence of clinical presentation on 3-year follow-up of patients with and without diabetes who had undergone a percutaneous coronary intervention (PCI) with drugeluting stent (DES) implantation. The study concludes that it demonstrates that diabetes mellitus patients have a worse prognosis, not depending on their clinical presentation which could be acute coronary syndrome (ACS) or stable angina.…”
mentioning
confidence: 99%